From Isolation to Interaction: How Cooperative Learning Role-Play Transforms Social Skills in Behaviorally Challenged Kindergarteners - Riwayati, Antin; Pamungkas, Bayu (Journal of Innovation and Research in Primary Education, 2025)
Children with behavioral barriers frequently experience significant challenges in developing appropriate social interaction skills, impacting their educational experiences and peer relationships. Traditional instructional approaches often inadequately address the specific needs of these children in developing essential social competencies. This study investigated the effectiveness of cooperative learning role-playing methods in enhancing social interaction capabilities among behaviorally challenged kindergarten children. A classroom action research design was employed over four weeks at TK Negeri 1 Sangatta Selatan, involving 15 children aged 5-6 years from Group B, with four children specifically identified as having behavioral barriers. The intervention consisted of structured role-playing activities within cooperative learning frameworks, implemented across two cycles with multiple sessions. Data collection utilized structured observation sheets assessing five key dimensions: communication abilities, sharing behaviors, cooperation skills, emotional regulation, and problem-solving capabilities. Assessment employed a four-point developmental scale from "Not Yet Developed" to "Developing Very Well." Significant improvements in social interaction capabilities were observed across all intervention phases. Mean social interaction scores increased progressively from 41.3% at baseline to 63% following Cycle I, and ultimately reached 83% after Cycle II completion, representing a total improvement of 41.7%. The final achievement exceeded the predetermined 80% success criterion, with 60% of children attaining "Developing Very Well" status and 33.3% reaching "Developing as Expected" levels. Cooperative learning role-playing methods effectively enhance social interaction skills among children with behavioral barriers in kindergarten settings. The structured peer-mediated approach provides practical, classroom-implementable solutions for addressing behavioral challenges while promoting inclusive educational practices. The findings support integration of social-emotional learning within mainstream early childhood curricula.